2019
DOI: 10.3390/biom9060207
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Protein Denaturation and Enzyme Inhibitors on Proteasomal-Mediated Production of Peptides in Human Embryonic Kidney Cells

Abstract: Peptides produced by the proteasome have been proposed to function as signaling molecules that regulate a number of biological processes. In the current study, we used quantitative peptidomics to test whether conditions that affect protein stability, synthesis, or turnover cause changes in the levels of peptides in Human Embryonic Kidney 293T (HEK293T) cells. Mild heat shock (42 °C for 1 h) or treatment with the deubiquitinase inhibitor b-AP15 led to higher levels of ubiquitinated proteins but did not signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…LC-MS and LC-MS/MS experiments were performed in an Orbitrap (OT) Fusion Tribrid mass spectrometer (Thermo Fisher Scientific, Waltham, MA, U.S.A) within the facilities at Harvard Medical School while using similar conditions to those previously described [81]. Briefly, OT top speed data-dependent precursor ion selection was used.…”
Section: Mass Spectrometry and Data Analysesmentioning
confidence: 99%
“…LC-MS and LC-MS/MS experiments were performed in an Orbitrap (OT) Fusion Tribrid mass spectrometer (Thermo Fisher Scientific, Waltham, MA, U.S.A) within the facilities at Harvard Medical School while using similar conditions to those previously described [81]. Briefly, OT top speed data-dependent precursor ion selection was used.…”
Section: Mass Spectrometry and Data Analysesmentioning
confidence: 99%
“…The majority of HEK293 and and human neuroblastoma SH-SY5Y cell peptides identified during peptidome studies were likely to be generated by proteasomes, as they are fragments of intracellular proteins, mostly containing from 5 to 17 amino acids in length and having either a hydrophobic (75%), basic (12%), or acidic (8%) amino acids at their C terminus [ 95 ]. Thus, InPeps’ profile was shown to be strongly modulated by proteasome inhibition, both in HEK293 and SH-SY5Y cells and murine brain [ 72 , 80 , 81 , 96 , 97 , 98 , 99 , 100 ]. When considering the length of the endogenous substrates of THOP1, the majority of the substrates were peptides that were 9 to 11 amino acids long.…”
Section: Seminal Experiments Evidencing That Intracellular Peptidementioning
confidence: 99%
“…These studies also demonstrated that the overexpression of THOP1, which has been shown to be involved in the metabolism of specific intracellular peptides [53] and modulation of signal transduction of angiotensin II (AT1) and β-adrenergic GPCR in CHO and HEK293 cells. Recent studies in HEK293 cells showed that most of these intracellular peptides are generated by the proteasome, where additional intracellular peptide-generating peptidases also exist [52,[54][55][56].…”
Section: Brief Historical Perspective On Proteasome-derived Intracellmentioning
confidence: 99%
“…Intracellular peptides are mainly generated by proteasome [55,56,[60][61][62][63] and should function inside the cells, possibly regulating protein interactions [43,54,64,65]. However, a significant portion of intracellular peptides can be secreted [66], suggesting that they can also act on membrane receptors [67,68].…”
Section: Brief Historical Perspective On Proteasome-derived Intracellmentioning
confidence: 99%